(untitled) (Global Journal of Computer Science and Technology, 2023)
In today s software development environment the necessity for providing quality software products has undoubtedly remained the largest difficulty As a result early software bug prediction in the development phase is critical for lowering maintenance costs and improving overall software performance Clustering is a well-known unsupervised method for data classification and finding related patterns hidden in datasets